Synthesis of d-fructose conjugated ligands via C6 and C1 and their corresponding [Ru(bpy)2(L)]Cl2 complexes. (29th June 2017) - Pröhl, Michael; Moser, Pascal D.; Czaplewska, Justyna A.; Hoffmann, Patrick; Buś, Tanja; Traeger, Anja; Goerls, Helmar; Schubert, Ulrich S.; Gottschaldt, Michael
Abstract: A pyridyl triazole (pyta) modified sucrose ligand was prepared in a seven step synthesis usingd -glucose as the protection group ford -fructose and starting from commercially available sucrose. After complexation with Ru(bpy)2 Cl2 precursor, the sucrose-conjugated Ru complex of the general formula [Ru(bpy)2 (L)]Cl2 was formed. Acidic cleavage of thed -glucose unit led to the firstd -fructose conjugated metal complex via d -fructose C6 in literature. Additionally, pyta-modifiedd -fructose via C1 and the corresponding Ru complex were synthesized. All compounds were analyzed by Rf values, specific rotation, NMR, IR, UV/Vis and fluorescence spectroscopy, mass spectrometry and elemental analysis. Graphical abstract: Highlights: Sucrose can be used as a starting material for the modification of the C6 position ofd -fructose. Pyridyl triazole (pyta) was introduced to the C1 and to the C6 position ofd -fructose to form a potential chelating ligand. d -fructose conjugated pyta form complexes of the general formula [Ru(bpy)2 (L)]Cl2, when reacted with Ru(bpy)2 Cl2 .